Intrinsically Radiolabeled Nanoparticles: An Emerging Paradigm - Goel, Shreya (2014)
Although chelator-based radiolabeling techniques have been used for decades, concerns about the complexity of coordination chemistry, possible altering of pharmacokinetics of carriers, and potential detachment of radioisotopes during imaging have driven the need for developing a simple yet better technique for future radiolabeling. Here, the emerging concept of intrinsically radiolabeled nanoparticles, which could be synthesized using methods such as hot-plus-cold precursors, specific trapping, cation exchange, and proton beam activation, is introduced. Representative examples of using these multifunctional nanoparticles for multimodality molecular imaging are highlighted together with current challenges and future research directions. Although still in the early stages, design and synthesis of intrinsically radiolabeled nanoparticles has shown attractive potential to offer easier, faster, and more specific radiolabeling possibilities for the next generation of molecular imaging.